Analyzing Challenges Faced by Students in Learning Vocabulary at Seventh Grade of MTs Qamarul Huda Bagu - Hidayatullah, Hidayatullah; Hasbullah, Hasbullah; Herman, Herman (Tirai Edukasi : Jurnal Pendidikan, 2025)
This study investigates the challenges faced by seventh-grade students at MTs Qamarul Huda Bagu in mastering English vocabulary. Vocabulary mastery is essential for developing the four core language skills: listening, speaking, reading, and writing. However, many students struggle with comprehension, retention, and practical application of vocabulary in real-life contexts. A qualitative case study was employed, combining online surveys of 22 students and interviews with English teachers, supplemented by documentation. Thematic analysis revealed five key challenges: difficulty understanding new vocabulary, frequent forgetting of learned words, boredom during lessons, shyness or lack of confidence, and limited opportunities to use English outside the classroom. Teachers also highlighted gaps in students’ initial abilities and limitations in technological resources. Nevertheless, contextual teaching and learning (CTL), interactive games, songs, and visual media proved effective in engaging students. Findings suggest that vocabulary learning strategies must integrate multimedia tools, psychological support, and increased practice opportunities. This study underscores the importance of varied pedagogical approaches and supportive environments in enhancing vocabulary mastery